Time- and Race-Specific Haematological Reference Intervals for Healthy Volunteer Trials: A Retrospective Analysis of Pooled Data From Multiple Phase I Trials - Coates, Simon; Wang, Duolao; Pierscionek, Tomasz; Fernandes, Sara; Djumanov, Dilshat; Lorch, Ulrike; Täubel, Jörg (Frontiers in Pharmacology, 2020)
Most UK hospitals, laboratories and research institutions use uniform reference intervals (RI) that do not take into account known diurnal and racial variation in total WBC and its constituent parameters. This risks excluding potentially suitable ethnic minority volunteers from participating in phase I clinical trials and could call into question the validity of a trial’s findings or limit its scientific applications and ability to accurately observe drug effects upon WBC parameters. This study pools data from multiple phase I trials, assesses the effects of race and time of day on WBC, and compares this to existing literature, to establish race and time specific reference intervals. 13,332 venous blood samples obtained from 7157 healthy male and female volunteers at the time of screening or admission (pre-dosing) who took part in 35 Phase I trials over a period of seven years were pooled and the data analysed by generalised estimating equation models. Adjusted RI of total WBC count and its individual parameters were then calculated according to time of day (morning vs evening) for both black and non-black populations. This study indicates that black individuals on average had lower total WBC, neutrophil, monocyte, eosinophil and basophil counts than individuals from non-black racial groups. Black volunteers had higher mean lymphocyte counts relative to their non-black counterparts. These differences were deemed statistically significant. Statistically significant rises in total WBC, neutrophil, lymphocyte and monocyte counts were also observed over the course of daily sampling. Eosinophil counts decreased during this time period, though this finding was only statistically significant in the non-black population. Despite an observed mild diurnal increase in basophil count in both populations, this was not considered statistically significant. This high-powered study adds significant weight to the known evidence for diurnal and racial variation in WBC parameters. It proposes specific RIs that more precisely reflect race and time of day and may ensure increased participation of black volunteers in clinical trials as well as facilitating more accurate post-dose safety monitoring and reporting and ensuring more accurate monitoring of post-dose WBC count changes.